Scaling effects in structural-phase self-organization at the "thin film - substrate" interface; Physical Mesomechanics; Vol. 10, iss. 3-4, May-Aug. - Panin V. E. Viktor Evgenyevich; Panin A. V. Alexey Viktorovich; Sergeev V. P. Viktor Petrovich; Shugurov A. R. Artur Rubinovich (2007, 2007)
The paper demonstrates that at the "thin film - substrate" interface there occurs structural self-organization that reveals two levels of structural-phase scaling. The levels are governed by the formation of cluster and cellular mesostructures. We discuss the nature of structural-phase self-organization, the commonness of the obtained results and their importance for scientific and engineering applications